Providing a Model of Mental Shortcuts of Influential Users for Choosing Marketing Influencers on Instagram - Reza Rastegari; Abolghasem Ebrahimi; Alireza Amini (‫مدیریت بازرگانی, 2022)
Objective The purpose of this study was to explore the factors affecting users’ identification and selection of influencers on Instagram. Therefore, the study focused on the frequency and diversity of active influencers on Instagram as a social media platform. It sought to designate the key indicators and mental shortcuts employed by users to identify and select influencers before collaborating with them. Through empirical investigations, the study proposed a framework composed of effective factors. Methodology This study is an applied, developmental research that relies on an exploratory mixed (qualitative-quantitative) method. In the qualitative part of the study, the literature on the topic and existing documents were systematically reviewed. Next, based on the Morgan table for determining sample size in an infinite population, 384 users of influencer marketing strategy on the Instagram platform were asked to complete copies of a designed questionnaire. Equation structural modeling (ESM) was used to analyze the data collected. Findings After the content obtained through the qualitative stage was analyzed, 22 initial categories were observed, which were classified into seven final categories considering their conceptual similarities. The final categories represented users’ mental shortcuts when they tried to identify and select influences on Instagram. Following an analysis of the relationships among the categories, they were divided into level partitions, and their driving power and dependence power diagram were drawn. Conclusion This study proposed a final model of the factors as users’ mental shortcuts in identifying and selecting influencers for financial support and collaboration purposes. The model fit also revealed causal-hierarchical relationships among the factors.